Acute Lymphocytic Leukemia with Skin Infiltration. Case Report and Literature Review - Adrian Isacc Nieto Jiménez (Revista Finlay, 2022)
Cutaneous leukemia is a very rare pathology and can occur in different types of leukemia associated or not with genetic syndromes. It is a very uncommon form of initial presentation of malignancy. Due to its non-specific skin lesions and the similarity with various skin pathologies, it represents a great diagnostic challenge for the pediatric dermatologist. We present the case of a 5-year-old boy with a history of acute lymphocytic leukemia with scaly papular lesions of a lichenoid appearance disseminated in the cutaneous integument. A skin biopsy was performed on suspicion of skin infiltration or leukemia cutis. The case was discussed to reach diagnostic confirmation of cutaneous leukemia. Treatment was started in the Hematology Service. This hematological disease occasionally manifests itself on the skin and when it does, it is necessary to recognize it to complete its diagnosis and treatment and save the life of the affected patient, as in this case. The interest of this presentation lies in the fact that the appearance of skin lesions, even if they are non-specific, in a patient with leukemia, should alert the treating medical team for their rapid study and thus guide therapeutic behavior and due to their low incidence of presentation.